Environmental cost and environmental performance in Malaysian small-medium manufacturing enterprises - Muhammad Jamil, Che Zuriana; Mohamed, Rapiah (International Information Institute, 2016)
This paper examines the extent of environmental costs for Malaysian Small-Medium (SME) enterprises and the relationship of those costs with environmental performance and firm performance.A survey was administered to 350 Malaysian SMEs for manufacturing industry, which were derived from the directory of the Federation of Malaysian manufacturers (FMM). The response rate was 20 percent.The results indicate that SMEs in Malaysia incur environmental costs, and those costs have a positive significant effect on environmental performance.The study also shows that environmental performance mediates the relationship between environmental costs and firm performance.